Restricting extensions to permitted licensing hours does not influence the numbers of alcohol or assault related attendances at an inner city accident and emergency department. Issue 1 (January 1998) - Graham, C A; McLeod, L S; Steedman, D J
Abstract : OBJECTIVE: To determine the effect of restricting extensions to permitted licensing hours on the numbers of alcohol or assault related attendances at an inner city accident and emergency (A&E) department. METHODS: Prospective data collection on consecutive attendances between 17.00 and 09.00 h during three study periods: two weeks before the introduction of the restriction, two weeks immediately afterwards, and for a two week period beginning five weeks after the change. Blood alcohol concentration was measured with a pocket alcohol meter. RESULTS: Overall 56.5% of patients (n = 2836) provided a breath sample, and 28.9% (819) were positive. The proportion of patients testing positively peaked between 02.00 and 04.00 h. A very high proportion of assault cases who were tested (260) were positive (67.3%). Assault cases comprised 19.1% of all attendances between 24.00 and 04.00 h. No significant changes in the pattern of alcohol or assault related attendances followed the restriction in extensions to permitted licensing hours. CONCLUSIONS: A policy of uniform closing times of licensed premises does not influence the profile of alcohol or assault related attendances at an inner city A&E department.